Fluoride-free flame-retardant PC resin composition as well as preparation method and application thereof
Through the synergistic effect of the dual-nano network structure composed of gas-phase silica and multi-wall carbon nanotubes and silicone flame retardant, the problem of high modification cost and low impact strength of fluorine-free flame retardant PC system is solved, and high-level is achieved The flame retardant properties and excellent mechanical properties are suitable for a variety of electronic and automotive applications.
Patent Information
- Application Number
- CN202411589438.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fluorine-free flame retardant PC system has problems such as high modification cost, low impact strength, low melt strength and low flame retardant grade. It is especially difficult to meet environmental sustainability when replacing perfluoroalkyl compounds (PFAS). and performance requirements.
Through a dual-nano network structure composed of gas-phase silica and multi-wall carbon nanotubes, combined with a small amount of silicone flame retardant, a synergistic effect is formed to improve melt strength and flame retardant grade, achieving relatively low-cost halogen-free and fluorine-free flame retardant PC resin composition.
Effectively prevent droplets during combustion, improve the flame retardant level to V-0, while maintaining excellent mechanical properties, reducing modification costs, suitable for new energy batteries, office equipment, electronics, home appliances, and automobiles. field.
Smart Images

Figure BDA0005125176380000021 
Figure BDA0005125176380000051 
Figure BDA0005125176380000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a fluorine-free flame-retardant PC resin composition and a preparation method and application thereof. Background Art
[0002] PC resin has excellent flame retardancy and can meet the UL V-2 flame retardant standard by itself. Its limiting oxygen index is as high as 21%-24%. However, PC resin is easy to drip during combustion. In flame retardant modification, high molecular weight polytetrafluoroethylene (PTFE) is usually required as an anti-dripping agent to achieve the V-0 flame retardant requirement. However, PTFE, as a core component of the flame retardant system, inevitably contains perfluorinated and polyfluoroalkyl compounds (PFAS) during the polymerization process. Its chemical structure (CF bond) is extremely stable and can withstand high temperature, light, chemical action, microbial action, and the metabolism of higher vertebrates. It is called a "permanent chemical" and will accumulate permanently in the human body, posing a direct threat to health. At the same time, studies have shown that PFAS pollution is exacerbating the global biodiversity crisis.
[0003] As the understanding of the potential impact of PFAS deepens, it is expected that the global control of PFAS will become increasingly strict in the next few years. This will drive related industries to seek and develop alternative materials to PFAS to ensure the environmental sustainability of products. Scientists are conducting research on new PC / ABS flame retardant systems, hoping that the new PC / ABS flame retardant system can replace the vacancy caused by PTFE. At present, the more successful cases are silicone copolymer PC, silicone flame retardant and other silicone flame retardant systems, but this type of system will increase the modification cost by a huge amount. There are also fillers with flame retardant synergistic effects, such as glass fiber, talc, nano-montmorillonite, wollastonite, etc., but although this type of system can also achieve a stable flame retardant effect, the impact strength is low, which affects the terminal use.
[0004] Chinese patent CN107663366A discloses a carbon nanotube reinforced halogen-free flame-retardant PC / ABS composite material and its molded products. The composite material includes PC resin, ABS resin, flame retardant, surface-treated carbon nanotubes and reinforcing material by weight, wherein the reinforcing material includes silicon dioxide. The halogen-free flame-retardant PC / ABS composite material has excellent mechanical properties, and the flexural strength and flexural modulus can be improved by about 30%, the notched impact strength can be improved by more than 20% and at the same time has V-0 grade flame retardant performance, but the composite material cannot effectively meet the requirements of PFAS (perfluoroalkyl compounds)-free. Summary of the invention
[0005] The purpose of the present invention is to provide a fluorine-free flame-retardant PC resin composition and a preparation method and application thereof, so as to overcome the problems of high modification cost, low impact strength, low melt strength and low flame retardancy of the fluorine-free flame-retardant PC system in the prior art.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] In one aspect, the present invention provides a fluorine-free flame-retardant PC resin composition, comprising the following components in parts by weight:
[0008]
[0009] Preferably, the PC resin is bucket-grade PC, and the melt index of the PC resin at 300° C. and a load of 1.2 kg is 2-5 g / 10 min.
[0010] Further preferably, the bucket-grade PC resin refers to a polycarbonate PC material that can be used to manufacture drinking water buckets. This material needs to meet food contact safety standards and have excellent transparency, heat resistance, impact resistance, and dimensional stability.
[0011] Further preferably, the PC resin has a melt index of 2-3 g / 10 min, which improves melt strength and reduces droplets during combustion.
[0012] Preferably, the phosphorus content of the phosphazene flame retardant is greater than 13 wt%.
[0013] Further preferably, the phosphazene flame retardant includes hexaphenoxy cyclophosphazene.
[0014] Preferably, the particle size of the fumed silica is between 150 nm and 350 nm.
[0015] Preferably, the specific surface area of the fumed silica is 150-400m 2 / g.
[0016] Preferably, the diameter of the multi-walled carbon nanotubes is 10 nm-20 nm.
[0017] Preferably, the specific surface area of the multi-walled carbon nanotubes is 200-400 m 2 / g.
[0018] Preferably, the organosilicon compound is selected from one or more of octaphenylcyclotetrasiloxane and cage-shaped polysilsesquioxane.
[0019] More preferably, the methyl substitution rate of phenyl in the organosilicon flame retardant is greater than 80%.
[0020] Preferably, the toughening agent is a silicon-containing acrylic core-shell toughening agent.
[0021] Further preferably, the silicone acrylate rubber is used as the core and its content is 50wt%-65wt%.
[0022] Further preferably, the shell of the silicon-containing acrylic core-shell toughening agent is methyl methacrylate-styrene copolymer.
[0023] More preferably, the particle size of the silicone acrylate rubber is 150nm-300nm.
[0024] Further preferably, the silicone acrylate rubber has a silicon content of 30 wt % to 70 wt %.
[0025] Preferably, the auxiliary agent is selected from a mixture of one or more of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene bis stearamide, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber.
[0026] Further preferably, the silane coupling agent includes epoxy silane, vinyl silane, amino silane, and methacryloxy silane.
[0027] Further preferably, the titanate coupling agent includes a monoalkoxy titanate coupling agent, a monoalkoxy pyrophosphate titanate coupling agent, an integrated titanate coupling agent, and a ligand titanate coupling agent.
[0028] More preferably, the hindered phenol antioxidant includes Irganox 1076, Irganox 1010, Irganox 1098, Irganox 300, Irganox 1790, and Irganox B900.
[0029] More preferably, the phosphite antioxidant includes Irgafos 168, Irgafos 626, Irgafos 619, Irgafos P-EPQ and Irgafos 9228.
[0030] Further preferably, the benzotriazole UV absorber includes UV-P, UV-329, UV234, UV-326, UV-360, and UV-327.
[0031] In a second aspect, the present invention further provides a method for preparing the above-mentioned fluorine-free flame-retardant PC resin composition, comprising the following steps:
[0032] S1, weighing each component by weight, and mixing them uniformly to obtain a mixed raw material;
[0033] S2. The mixed raw material obtained in step S1 is sheared and kneaded by a twin-screw extruder. The mixed raw material is melted, compounded, extruded, drawn, cooled and pelletized to obtain the fluorine-free flame-retardant PC resin composition; the screw aspect ratio of the twin-screw extruder is (35-50):1, the screw speed is 300-500 rpm, and the extrusion temperature is 260-280°C.
[0034] Preferably, the mixing is performed in a high-speed mixer.
[0035] More preferably, the rotation speed of the high-speed mixer is 300 rpm to 500 rpm.
[0036] Further preferably, the screw aspect ratio of the twin-screw extruder is 40:1.
[0037] Further preferably, the screw rotation speed is 400 rpm.
[0038] In a third aspect, the present invention also provides an application of the fluorine-free flame-retardant PC resin composition in new energy batteries, automobiles, electronic products, furniture decoration, and office equipment.
[0039] Further preferably, the fluorine-free flame-retardant PC resin composition can be used for the manufacture of black specific parts in new energy batteries, automobiles, electronic products, furniture decoration, and office equipment.
[0040] Further preferably, the fluorine-free flame-retardant PC resin composition can be applied to the manufacture of electric vehicle battery chargers.
[0041] Further preferably, the fluorine-free flame-retardant PC resin composition can be used to manufacture automotive interior black trims such as dashboards, door panels, etc., automotive exterior black parts such as bumpers, hub covers, etc., automotive electronic equipment housings such as vehicle infotainment systems, vehicle communication equipment, etc.
[0042] More preferably, the fluorine-free flame-retardant PC resin composition can be used in black parts such as housings, bases and keyboards of smart phones, tablet computers, laptop computers and the like.
[0043] Further preferably, the fluorine-free flame-retardant PC resin composition can be used in the manufacture of frames and supporting parts of tables, chairs, and sofas.
[0044] Further preferably, the fluorine-free flame-retardant PC resin composition can be used in the manufacture of black parts of printers and copiers, such as housings and internal structural parts, to provide heat-resistant and flame-retardant protection.
[0045] The purpose of the present invention is to effectively prevent molten droplets during combustion by flame retardant synergy of fumed silica and carbon nanotubes with a small amount of silicone, and the double nano-network structure composed of fumed silica and carbon nanotubes is particularly effective in improving melt strength, thereby achieving a relatively low-cost black halogen-free and fluorine-free flame retardant PC solution for specific applications, while also having excellent mechanical properties.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] (1) The present invention mainly prevents the melting droplet phenomenon of PC during the combustion process by using a double nano-network structure composed of fumed silica and multi-walled carbon nanotubes. Combined with a small amount of organic silicon flame retardant, the overall flame retardancy level is greatly improved, the modification cost of the fluorine-free flame retardant PC system is reduced, and at the same time, it has excellent mechanical properties.
[0048] (2) The present invention can greatly improve the melt strength of the flame retardant system through the double nano-network structure composed of fumed silica and carbon nanotubes, thereby effectively preventing the phenomenon of molten droplets during the combustion process.
[0049] (3) The present invention can achieve a V-0 flame retardant grade through the synergistic effect between fumed silica and carbon nanotubes and a small amount of organic silicon flame retardant, while maintaining excellent mechanical properties and having good impact strength.
[0050] (4) The present invention provides a relatively low-cost halogen-free and fluorine-free flame-retardant PC solution for specific black applications (carbon nanotubes have their own black properties), which is suitable for application in new energy batteries, office equipment, electronics, home appliances, automobiles and other fields. DETAILED DESCRIPTION
[0051] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0052] The components and characteristics involved in the embodiments and comparative examples of the present invention are as follows:
[0053] PC resin, M7027, Sinopec Mitsubishi, melt index 3g / 10min;
[0054] Phosphazene flame retardant, WSFR-5101, Zhejiang Wansheng;
[0055] Toughening agent, MR01, Kaneka Chemical, Japan;
[0056] Fumed silica, M-5, Cabot, surface area 200m 2 / g;
[0057] CNT, 210T, Kumho, South Korea, surface area 250-280m 2 / g;
[0058] Silicone flame retardant-1: FR800, octaphenylcyclotetrasiloxane, Puxin polymer;
[0059] Silicone flame retardant-2: FR300, methylphenyl cyclotetrasiloxane, phenyl substitution rate less than 80%, Puxin polymer;
[0060] Talc, 3CA, Yirui stone;
[0061] Antioxidant, Irganox B900, BASF;
[0062] Lubricant, PETS, AHS, Italian hair base.
[0063] Table 1 Composition of Examples 1 to 5 and Comparative Examples 1 to 8
[0064]
[0065]
[0066] Examples 1 to 5 and Comparative Examples 1 to 8
[0067] PC resin, phosphazene flame retardant, toughening agent, fumed silica, CNT, silicone flame retardant and additives were weighed according to the weight parts in Table 1, stirred and fully mixed in a high-speed mixer, and then sent to a twin-screw extruder through a metering device. Under the conveying, shearing and mixing of the screw, the materials were melted, compounded, homogenized, drawn, cooled and pelletized to obtain a fluorine-free flame-retardant PC resin composition.
[0068] The twin-screw extruder has a screw length-to-diameter ratio of 40:1 and is equipped with a temperature control device and a vacuum device. The extrusion temperature of the twin-screw extruder is 260-280°C and the screw speed is 400 rpm.
[0069] The fluorine-free flame-retardant PC resin compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 8 were subjected to performance tests. The test results are shown in Table 2.
[0070] The test methods of various embodiments and comparative examples are described as follows:
[0071] The tensile strength test was carried out according to ASTM D638 standard, and the test speed was 50 mm / min.
[0072] The notched impact strength test was carried out according to ASTM D256.
[0073] The melt index test was carried out according to ASTM D1238 standard, with a load of 5 kg and a test temperature of 240°C.
[0074] The flame retardant test is carried out according to UL94 standard.
[0075] Table 2 Performance of Examples 1 to 5 and Comparative Examples 1 to 8
[0076]
[0077] As can be known from each embodiment 1-5 of Table 1 and 2, the present invention adopts fumed silica and CNT to produce a dual nano-network structure in a flame-retardant matrix, greatly enhancing the melt strength of the system, and can produce a good flame-retardant synergistic effect with a high phenyl siloxane flame retardant, and can effectively control the melting drop phenomenon of flame-retardant PC during combustion, play a similar anti-dripping effect of PTFE, and achieve V-0 flame retardant grade, while maintaining excellent mechanical properties. Thus, it can be known from comparative examples 1-6 that when fumed silica and CNT are used alone to form a single network structure, or not coordinated with a high phenyl siloxane flame retardant, substantial damage will be produced to flame retardancy, and a stable flame retardant grade of V-0 can not be achieved. As can be known from comparative examples 7 and 8, when talcum powder is used to replace fumed silica, or when methylphenylcyclotetrasiloxane with a low phenyl substitution rate is used, a good synergistic flame retardant effect can not be achieved.
[0078] The fluorine-free flame-retardant PC resin composition of the present invention not only has excellent mechanical properties, but also has excellent flame retardant stability, achieving V-0 grade flame retardancy, and is very suitable for use in new energy batteries, office equipment, electronic and electrical equipment, home appliances, automobiles and other fields.
Claims
1. A fluorine-free flame-retardant PC resin composition, characterized in that: The composition comprises the following components in parts by weight:
2. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The PC resin is bucket-grade PC, and the melt index of the PC resin at 300° C. and 1.2 kg load is 2-5 g / 10 min.
3. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The phosphorus content of the phosphazene flame retardant is greater than 13 wt %, and the phosphazene flame retardant includes hexaphenoxy cyclophosphazene.
4. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The particle size of the fumed silica is between 150nm and 350nm, and the specific surface area is between 150 and 400m 2 / g.
5. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The multi-walled carbon nanotubes have a diameter of 10 nm to 20 nm and a specific surface area of 200 to 400 m 2 / g.
6. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The organic silicon flame retardant is selected from one or more of octaphenylcyclotetrasiloxane and cage-shaped polysilsesquioxane.
7. A fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The toughening agent is a silicon-containing acrylate core-shell toughening agent, wherein the organic silicon acrylate rubber is used as the core, the content thereof is 50wt%-65wt%, the particle size is 150nm-300nm, and the silicon content thereof is 30wt%-70wt%.
8. The fluorine-free flame-retardant PC resin composition according to claim 1, characterized in that: The auxiliary agent is selected from a mixture of one or more of silane coupling agent, titanate coupling agent, hindered phenol antioxidant, phosphite antioxidant, ethylene bis stearamide, polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and benzotriazole UV absorber.
9. A method for preparing a fluorine-free flame-retardant PC resin composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, weighing each component by weight, and mixing them uniformly to obtain a mixed raw material; S2. The mixed raw material obtained in step S1 is sheared and kneaded by a twin-screw extruder. The mixed raw material is melted, compounded, extruded, drawn, cooled and pelletized to obtain the fluorine-free flame-retardant PC resin composition; the screw aspect ratio of the twin-screw extruder is (35-50):1, the screw speed is 300-500 rpm, and the extrusion temperature is 260-280°C.
10. Use of the fluorine-free flame-retardant PC resin composition according to any one of claims 1 to 8 in new energy batteries, automobiles, electronic products, furniture decoration, and office equipment.
